Barriers against incorporating evidence-based practice in physical therapy in Colombia: current state and factors associated. Issue 1 (December 2015) - Ramírez-Vélez, Robinson; Bagur-Calafat, M.; Correa-Bautista, Jorge; Girabent-Farrés, Montserrat
Abstract Background Evidence-based practice (EBP) has been widely implemented in differing areas of physiotherapy. Nevertheless, few studies have investigated EBP-related barriers amongst Latin-American physical therapists working in primary care. The primary objective of this study was to describe the current state concerning perceived barriers engagement in EBP among physical therapy in Colombia. A secondary objective was to identify factors associated with barriers to implementation EBP. Methods A cross-sectional online survey was conducted. The study involved physical therapists working in public and private hospital who were contacted through professional networks (Email, Facebook®, ResearchGate® and Linked-In® ) and invited to participate. Multiple logistic regression (MLR) and multiple correspondence analysis (MCA) were used for examining factors associated with perceived barriers to including EBP in their work. Results The final sample size was 1064 (77.2 % female). Forty-one percent of the respondents indicated that a "lack of research skills" was the most important barrier to evidence being used in practice. MLR analysis suggested that several variables were associated with perceived barriers to including EBP: i.e. hours of work per week, current main role in therapy center and undergraduate degree. The MCA model established two groups of similarities regarding the different barriers; the "lack of understanding of statistical analysis", "insufficient time" and "understanding of the English in which articles are written" barriers were weighted more heavily regarding in the first group (the second factor on MCA) and the rest barriers on the second group (first factor on the MCA). Conclusions Although most physiotherapists had a positive opinion regarding EBP, they considered that they needed to improve their knowledge, skills and attitudes towards EBP. Initiatives to advance EBP in Colombia with no academic or research tradition should primarily target practitioner-level factors.